Speaking with Policymakers About Current Issues - Alexa J. Lamm (EDIS)
The future of the agricultural and natural resource industry requires that educators, industry professionals, and policymakers work together when addressing contentious issues. However, discussing contentious issues with policymakers at the local, state, and national level is not always an easy task. Policymakers in general are busy people with many issues competing for their limited time. Once in the door, it is important to deliver strong messages in the right way for the policymaker to listen and use your information when making important decisions. This 2-page fact sheet discusses the differences between education and persuasion and when to use each, offers information on how to make presentations that will get their attention, and identifies things to avoid when visiting with a policymaker. Written by Alexa J. Lamm and published by the UF Department of Agricultural Education and Communication, August 2013.